Cash crops and food security: Evidence from Ethiopian smallholder coffee producers - Kuma, Tadesse; Dereje, Mekdim; Hirvonen, Kalle; Minten, Bart (International Food Policy Research Institute, 2016)
One of the key questions in food policy debates in the last decades has been the role of cash cropping for achieving food security in low income countries. We revisit this question in the context of smallholder coffee production in Ethiopia. Using unique data collected by the authors on about 1,600 coffee farmers in the country, we find that coffee income improves food security, even after controlling for total income and other factors and after addressing the endogeneity of coffee income. Further analysis suggests that the pathway for achieving this improved food security is linked to being better able to smooth consumption across agricultural seasons. In contrast with food crops, coffee sales take place almost throughout the whole year, providing farmers with cash income also during the lean season.